Dinamisasi Pesantren Perspektif KHAS dalam Konstruksi Majalah Pesantren Tahun 1985 - Kun Wazis (Jurnal Al-Tatwir, 2019)
The perspective of a Kyai (a Javanese expert in Islam) in critically perceiving Islamic scholars becomes an important discourse in the changing face of Pesantren (Islamic boarding schools) from time to time. Kyai Haji Ahmad Shiddiq (KHAS) was one of the most notable figures who had extensive experiences in establishing this classical Islamic institution specific to Indonesia. In order to accentuate the great services of the late Jember figure, the State Islamic Institute of Jember (IAIN Jember) proposed the name KHAS as the new identity for the proposed institutional change status to become State Islamic University (UIN). This study attempted to explain KHAS’ perspective on Ulama (Islamic scholars) and Pesantren whose original thoughts were written in Pesantren Magazine in 1985. Employing a qualitative approach, focusing on text analysis of KHAS’ articles, an overview was obtained about the credibility of Ulama, the identity of Kyai, and the dynamics of Pesantren in Indonesia at that time and in the future to come. The results of the current study confirmed three important things. First, Ulama inherit the leadership roles of the Prophet Muhammad PBUH in terms of knowledge, deed, and morality. Second, the identity of a Kyai is presented to individuals who have reached the level of Ulama. Third, the dynamics of Pesantren community are carried out with two types of improvement, namely recovery and development.